2005
DOI: 10.1002/clc.4960281109
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of low-density lipoprotein particle size measurement in cardiovascular disease prevention

Abstract: SummaryBackground: Cardiovascular disease is largely explained by the traditional risk factors, but there are several novel risk factors that have been shown to predict cardiovascular morbidity. The measurement of low-density lipoprotein particle size (LDLPS) is a novel cardiovascular risk factor, yet it is unknown whether this measurement provides additional information that may influence the subsequent medical treatment of patients.Hypothesis: The measurement of LDLPS provides additional information that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Population density distributions of TC, HDL‐C, TG, Friedewald LDL‐C, non–HDL‐C, and the TC to HDL‐C ratio (Figure ) are nearly identical as shown by superimposable curves of lipid distributions from adults in the VLDL database and population‐representative National Health and Nutrition Examination Survey (NHANES) 2007 to 2008. In VLDL adults, the median directly measured LDL‐C is 108 mg/dL (2.79 mmol/L) and IQR 85 to 135 mg/dL (2.20–3.49 mmol/L).…”
Section: Vldl Populationmentioning
confidence: 89%
See 1 more Smart Citation
“…Population density distributions of TC, HDL‐C, TG, Friedewald LDL‐C, non–HDL‐C, and the TC to HDL‐C ratio (Figure ) are nearly identical as shown by superimposable curves of lipid distributions from adults in the VLDL database and population‐representative National Health and Nutrition Examination Survey (NHANES) 2007 to 2008. In VLDL adults, the median directly measured LDL‐C is 108 mg/dL (2.79 mmol/L) and IQR 85 to 135 mg/dL (2.20–3.49 mmol/L).…”
Section: Vldl Populationmentioning
confidence: 89%
“…For population‐based treatment purposes, worldwide guidelines predominantly categorize patients according to low‐density lipoprotein cholesterol (LDL‐C) levels, estimated by the Friedewald equation . However, there is great interest in further refining categorizations of abnormal lipid metabolism . Although levels of high‐density lipoprotein cholesterol (HDL‐C) and triglycerides (TG) are most commonly used for assessment beyond LDL‐C, even more granularity to lipid characterization is possible by using multiple complementary methods.…”
Section: Introductionmentioning
confidence: 99%
“…nHDL-C has been demonstrated to be a stronger predictor for CVD risk than traditional LDL-C [17], and elevated levels were still associated with an increased risk of coronary heart disease with LDL levels below 100 mg/dl [18]. However, many individuals who reach their respective nHDL-C targets nevertheless still possess an atherogenic lipid profile with residual risk [19]. Recent studies demonstrated that apoB may be superior to both nHDL-C and LDL-C as a predictor of CVD [20].…”
mentioning
confidence: 99%
“…LipoScience was initially dedicated to performing research on NMR-based cholesterol testing using plasma and serum samples. This effort eventually led to the development of a successful FDA-approved LDL test called LipoProfile in 2005 [ 63 ]. The LipoProfile NMR test is highly automated and provides 11 different measures of lipoprotein concentrations and sizes from plasma samples.…”
Section: Lipoprotein Profiling and Nmrmentioning
confidence: 99%